PENDIDIKAN ANTI KORUPSI MAMPU MEMOTIVASI MAHASISWA DALAM UPAYA PENCEGAHAN DAN PEMBERANTASAN PERBUATAN TINDAK PIDANA KORUPSI - Muzayanah (Ganesha Law Review, 2022)
Education that is carried out is certainly a learning process for humans that is carried out continuously so that humans become individuals who have perfection both physically and mentally. Education has a goal to produce strong individuals, do not do Collusion, Corruption and Nepotism which we know as KKN, humans who are responsible and have good morals and good morals, are independent, so with the hope that education will educate the nation's life and have a very important role. strategic. As we all know that corruption in Indonesia is very worrying and has an extraordinary negative impact in almost all aspects of life. Corruption also destroys the economic system, democratic system, political system, legal system, government system and social order as a whole. On the other hand, efforts to eradicate corruption have not been able to show maximum results as desired by the Indonesian people. Considering that corruption is an extraordinary crime, it requires serious efforts to eradicate it. Efforts to eradicate corruption are carried out through two things, namely: 1. Enforcement and 2. Prevention, which of course will not be easy to implement and succeed if only the government does it without the participation of the community. Therefore, it is something that can be done and not excessive if students who are an important part of society as the next generation of the Indonesian nation in the future are expected to be able and capable and active in efforts to prevent and eradicate acts of corruption in Indonesia.